2009
DOI: 10.1016/s1081-1206(10)60244-x
|View full text |Cite
|
Sign up to set email alerts
|

Repeated hospital encounters for asthma in children and exposure to traffic-related air pollution near the home

Abstract: Background: Aggregate hospital encounters for asthma (admissions or emergency department visits) have been associated with daily regional air pollution. There are fewer data on relationships between repeated hospital encounters and traffic-related air pollution near the home.Objective: To estimate the association of local traffic-generated air pollution with repeated hospital encounters for asthma in children.Methods: Hospital records for 2,768 children aged 0 to 18 years (697 of whom had Ն2 encounters) were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
2
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(87 citation statements)
references
References 40 publications
(59 reference statements)
2
81
2
2
Order By: Relevance
“…This is not consistent with other studies [18,19]. Passive tobacco smoking and exposure to outdoor dust and smoke were significant risk factors in the prevalence of asthma but had no significant effect on the need for hospital admission in our study, whereas other studies showed that exposure to smoke increased the severity of asthma and the need for hospital admission [14,20]. These differences between our study and others may be due to the small number of cases in our study, and ‫املتوسط‬ ‫لرشق‬ ‫الصحية‬ ‫املجلة‬ ‫عرش‬ ‫التاسع‬ ‫املجلد‬ ‫السادس‬ ‫العدد‬ the small numbers hospitalized, which may have affected the likelihood of findings significant differences.…”
Section: Risk Factors For Hospitalizationcontrasting
confidence: 99%
“…This is not consistent with other studies [18,19]. Passive tobacco smoking and exposure to outdoor dust and smoke were significant risk factors in the prevalence of asthma but had no significant effect on the need for hospital admission in our study, whereas other studies showed that exposure to smoke increased the severity of asthma and the need for hospital admission [14,20]. These differences between our study and others may be due to the small number of cases in our study, and ‫املتوسط‬ ‫لرشق‬ ‫الصحية‬ ‫املجلة‬ ‫عرش‬ ‫التاسع‬ ‫املجلد‬ ‫السادس‬ ‫العدد‬ the small numbers hospitalized, which may have affected the likelihood of findings significant differences.…”
Section: Risk Factors For Hospitalizationcontrasting
confidence: 99%
“…(5) and (6), the YAV indicator allows easy evaluations of pollutant emission loads discharged by a specific transportation system, even in correspondence of several hypothetical scenarios in turn correlated to different values of N tot | Ty c and L c .…”
Section: Emission Assessmentmentioning
confidence: 99%
“…Indeed, an estimated 10 % of the global pollution is generated by road vehicles which are furthermore accountable for 20 % of the European anthropogenic CO 2 emissions [4], while local impact of various air pollutants generated by road traffic, such as CO, NOx SO 2 , and particulate matter with a diameter of 10 micrometres or less (PM 10 ), has been documented [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…O tráfego ainda foi responsável por 25 mil novos casos de bronquite crônica em adultos, mais de 290 mil casos de bronquite em crianças e 500 mil de ataques de asma 50 . Diversos outros estudos utilizaram métodos semelhantes [51][52][53] . Estudos deste tipo são viáveis para o município de São Paulo, sendo a maior dificuldade a qualidade dos dados disponíveis para a alimentação do modelo e sua vantagem é a possibilidade de análise, com alta resolução, de cenários envolvendo medidas de controle, como restrição do uso de veí-culos, mudança de combustíveis ou de perfil da frota.…”
Section: Avaliação Da Exposição à Poluição Relacionada Ao Tráfegounclassified